Meningkatkan Minat dan Hasil Belajar Kelistrikan Bodi dengan Model Pembelajaran Project Based Learning di Sekolah Menengah Kejuruan - Nadzar Saifudin; Dwi Jatmoko; Miftahudin Miftahudin; Ahmad Tarmidi; Ilham Dinar Akbar Cudino (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Vocational education in Indonesia plays a crucial role in improving the quality of a skilled workforce ready to face the challenges of the industrial world. One vocational field that receives special attention is the Light Vehicle Engineering (TKR) study program, where body electrical engineering is one of the main subjects taught. Body electrical engineering is a crucial aspect of vehicle maintenance and repair, where a thorough understanding of electrical engineering is essential for operating and repairing electrical systems within vehicles. However, in practice, obstacles are often encountered in the process of learning body electrical engineering, particularly in terms of student interest and learning outcomes. Many students feel a lack of interest in this subject, which causes them to not optimally absorb the material. One way to address this problem is to implement a learning model that can foster interest in learning and improve student learning outcomes. One such model is Project-Based Learning (PjBL). PjBL is a learning model that prioritizes active student involvement in completing real-life projects relevant to the material being studied. Through this model, students are expected to learn in a more applicable and enjoyable way, which in turn can improve their understanding and learning outcomes. This study aims to test the effectiveness of the PjBL learning model in increasing the interest and learning outcomes of electrical engineering of class XI students at SMK Taman Karya Madya Pertambangan Kebumen.